Design for London : experiments in urban thinking - Bishop, Peter, 1953-; Williams, Lesley, 1957- (UCL Press, 2020)
Design for London critically examines Design for London, the unique experiment in urban planning, design and strategic thinking set up in 2006 by Mayor Ken Livingstone and his Architectural Advisor, Richard Rogers.